ENGLISH LANGUAGE PROFICIENCY AND THE EXISTING CHALLENGES FOR PROSPECTIVE ACCOUNTING PROFESSIONALS IN THAILAND - Tantikul, Nattapan; Soranarak, Wanvitu; Indraprasit, Chutinuch (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2025)
Purpose – This paper aims to raise awareness of difficulties and inconsistencies in the requirements and the process of the English language testing systems used by some universities in Thailand, and to point out the importance of English language proficiency for the accounting professionals in the present-day world. Body of Knowledge – Since the Higher Education Commission (HEC) of Thailand announced a crucial policy to improve English proficiency standards for higher education students in 2016, all universities in Thailand have already set rules and prescribed their students to fulfill the requirements for English proficiency examination. However, it is rather obvious that the testing requirements of the English language testing systems at the present time are not good and effective as it should be. Thus, when the requirements and the process have been made easier or compromised, the graduates may be underprepared for the workforce and might encounter more challenges at work, especially for accounting professionals. Implications – Policymakers in both Thai government agencies and universities in Thailand may rely on the information provided in this study to formulate more effective solutions and work on additional long-term plans for improving Thai students’ English proficiency. Understanding the flaws of the current English language testing systems will also promote realization and discussion among current and prospective accounting students. Originality/Value – This paper contributes to literature and practice by demonstrating the major problems of the current English language testing systems. To the best of our knowledge, this article is the first to lay out several common requirements for English proficiency examination and their noticeably wide-ranging test scores used in some universities in Thailand. This fact might indicate that English proficiency standards for higher education students in Thailand may not be improved and good as expected.